How do you differentiate #y=(x+5)(2x-3)(3x^2+4)#?

Answer 1

#y'=(2x-3)(3x^2+4)+2(x+5)(3x^2+4)+6x(2x-3)(x+5)#

#y'=24x^3+63x^2-74x+28#

If #y=uvw#, where #u#, #v#, and #w# are all functions of #x#, then: #y'=uvw'+uv'w+u'vw# (This can be found by doing a chain rule with two functions substitued as one, i.e. making #uv=z#)
#u=x+5# #u'=1#
#v=2x-3# #v'=2#
#w=3x^2+4# #w'=6x#
#y'=(2x-3)(3x^2+4)+2(x+5)(3x^2+4)+6x(2x-3)(x+5)#
#y'=6x^3+8x-9x^2-12+6x^3+8x+30x^2+40+12x^3+60x^2-18x^2-90x#
#y'=24x^3+63x^2-74x+28#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

#dy/dx=24x^3+63x^2-74x+28#

#"expand the factors and differentiate using the "color(blue)"power rule"#
#•color(white)(x)d/dx(ax^n)=nax^(n-1)#
#y=(x+5)(2x-3)(3x^2+4)#
#color(white)(y)=6x^4+21x^3-37x^2+28x-60#
#rArrdy/dx=24x^3+63x^2-74x+28#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To differentiate the function ( y = (x+5)(2x-3)(3x^2+4) ), you can use the product rule of differentiation:

[ \frac{d}{dx}[f(x)g(x)h(x)] = f'(x)g(x)h(x) + f(x)g'(x)h(x) + f(x)g(x)h'(x) ]

  1. Find the derivatives of each term:

    • ( f(x) = x + 5 ) (first factor)
    • ( g(x) = 2x - 3 ) (second factor)
    • ( h(x) = 3x^2 + 4 ) (third factor)
  2. Find the derivatives of each factor:

    • ( f'(x) = 1 ) (derivative of ( x + 5 ))
    • ( g'(x) = 2 ) (derivative of ( 2x - 3 ))
    • ( h'(x) = 6x ) (derivative of ( 3x^2 + 4 ))
  3. Apply the product rule: [ y' = (1)(2x-3)(3x^2+4) + (x+5)(2)(3x^2+4) + (x+5)(2x-3)(6x) ]

  4. Simplify the expression to obtain the final derivative.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7